Augmenting Coral Growth on Breakwaters: A Shelter-Based Approach - Almog Ben Natan; Natalie Chernihovsky; Nadav Shashar (Coasts)
With the increasing global population and migration toward coastal regions, and the rising demand for coastal urbanization, including the development of living spaces, ports, and tourism infrastructure, the need for coastal defense structures (CDSs) is also increasing. Traditional CDSs, such as breakwaters, typically composed of hard units designed to block and divert wave and current energy, often fail to support diverse and abundant marine communities because of their impact on current and sediment transport, the introduction of invasive species, and the loss of natural habitats. Marine ecoengineering aims at increasing CDS ecological services and the development of marine organisms on them. In this study, carried out in a coral reef environment, we examined the relationship between coral colony protection levels and three factors related to their development, namely, coral fragment survival rate, larval settlement, and water motion (flow rate), across three distinct niches: Exposed, Semi-sheltered, and Sheltered. Coral survivability was assessed through fragment planting, while recruitment was monitored using ceramic settlement tiles. Water motion was measured in all defined niches using plaster of Paris Clod-Cards. Additionally, concrete barrier structures were placed in Exposed niches to test whether artificially added protective elements could enhance coral fragment survival. No differences were found in coral settlement between the niches. Flow rate patterns remained similar in Exposed and Sheltered niches due to vortex formation in the Sheltered zones. Survival analysis revealed variability between niches, with the addition of artificial shelter barriers leading to the highest coral fragment survival on the breakwater. This study contributes to the development of ways to enhance coral development with the goal of transforming artificial barriers into functional artificial reefs.